Pour une rhétorique du vieillissement - Edit Bors (Temporalités, 2013)
Mon évasion (2008) by Benoîte Groult is a woman’s autobiography that not only fits into the history of feminism but also represents a complex and nuanced femininity that constitutes the backbone of the development of a personality as well as of a certain way of talking about oneself. Women are usually shown through their human relationships, as members of a “couple”. This new (feminine?) way of talking about oneself also has consequences for the writing itself: aside from the constant shifting to an fro between the narrative and the narrator’s discourse, the structural discontinuity – interviews are inserted, a comic strip is rewritten), and the problems of naming the character, Groult’s text uses a variety of verb tenses and personal pronouns: there are parts in the present, the present perfect, the preterit, combined with first, third or second-person pronouns. As a result, the autobiographical space in Mon évasion is unusually intricate: narrative, interviews, comic strip and cover photograph all contribute, in their diversity, to creating a plurality of temporalities that bring along new ways of representing femininity.